How to estimate the policy preferences of party supporters: Disaggregating data from voting advice applications versus modeling survey responses. (December 2021) - Toshkov, Dimiter; Romeijn, Jeroen
Abstract: Valid and reliable estimates of the policy preferences of political parties' supporters are essential for the study of political representation. However, such estimates are not directly available from standard surveys of public opinion, which are typically representative by design only at the national level and rarely ask questions about public support for specific policies. In this article, we explore the possibility to use data from voting advice applications (VAA) to estimate the policy preferences of party supporters. To do that, first, we identify 10 questions on preferences towards issues of public policy that were asked around the same time and with similar wording in traditional surveys of public opinion and in VAAs fielded in Germany and in the Netherlands. Then we compare the VAA data disaggregated by political affiliation of the respondents to the survey data adjusted via multilevel regression modeling with poststratification (MRP). We find strong positive correlations between the estimates derived from both methods, especially after weighting the VAA data. Yet, point estimates are not always very close, and the match is sensitive to the treatment of neutral and 'don't know' answers. Overall, our results bode well for the validity of using VAA data in empirical research on political representation.